Case report: Clitoral adenocarcinoma in a mixed-breed female dog - Moss, Christina; Sugai, Nicole; Persons, Rebecca; Ciepluch, Brittany; Lahmers, Kevin; Cecere, Julie (Frontiers in Veterinary Science, 2023)
A 9-year-old, spayed female, mixed-breed dog was initially presented for evaluation of chronic dermatitis on the nasal planum where a clitoral mass was discovered as an incidental finding during the exam. No further investigation of the clitoral mass was undertaken due to other, significant dermal lesions and the lack of clinical significance of the mass at the time. However, approximately one month later the dog was presented to the Emergency Service for bleeding from the vulva. The clitoral mass was found to have prolapsed; the mass was manually reduced back into a position within the vulvar folds and maintained with a purse-string suture. The dog was referred to the Theriogenology Service for further investigation and removal. On follow-up evaluation the mass was noted to be multi-lobulated, ulcerated, cystic, and involving the clitoris but not the urethra. The urethra was easily catheterized, and no urinary abnormalities were found. No evidence of lymph node metastasis or hypercalcemia was noted prior to surgery. Ultrasonographic evaluation of the anal sacs was normal. The mass was removed, and histopathologic evaluation revealed a primary clitoral adenocarcinoma. On recheck evaluation one month later no evidence of metastasis or local recurrence was evident. Clitoral adenocarcinoma is a rarely reported neoplasm of the canine genital tract which shares many clinical, histopathological, and immunohistochemical features with canine apocrine gland anal sac adenocarcinoma. This case adds to the available knowledge on the condition, specifically regarding frequency of complications such as hypercalcemia and metastasis, as previous reports suggest that these are present at least 50% of the time.